2014
DOI: 10.1111/nyas.12361
|View full text |Cite
|
Sign up to set email alerts
|

The Ah receptor in stem cell cycling, regulation, and quiescence

Abstract: Processes that regulate quiescence, self-renewal, and senescence of hematopoietic stem cells (HSCs) are not well understood. Due in part to the ability of xenobiotic ligands to have persistent effects on the immune system in experimental animals, there has been much work to define a physiological role of the aryl hydrocarbon receptor (AhR) and relationships to human disease. Persistent AhR activation by dioxin, a potent agonist, results in altered numbers and function of HSCs in mice. HSCs from AhR null-allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 52 publications
2
50
0
Order By: Relevance
“…Results from a variety of laboratories over the past decade have revealed that the AHR has key roles in the development of cardiovascular, reproductive, and neural systems as well as in hematopoiesis and regulation of immune responses (Benedict, Lin, Loeffler, Peterson, & Flaws, 2000; Esser & Rannug, 2015; Gasiewicz, Singh, & Bennett, 2014; Kimura, Ding, & Tohyama, 2016; Lahvis et al., 2005; Quintana & Sherr, 2013; Singh et al., 2014; Stockinger, Di Meglio, Gialitakis, & Duarte, 2014). Some of these functions may involve natural or endogenous ligands such as metabolites generated by the microbiome, tryptophan metabolites, or lipid‐derived molecules (Bessede et al., 2014; Hubbard, Murray, & Perdew, 2015; McMillan & Bradfield, 2007; Moura‐Alves et al., 2014).…”
Section: Ahr Pathwaymentioning
confidence: 99%
“…Results from a variety of laboratories over the past decade have revealed that the AHR has key roles in the development of cardiovascular, reproductive, and neural systems as well as in hematopoiesis and regulation of immune responses (Benedict, Lin, Loeffler, Peterson, & Flaws, 2000; Esser & Rannug, 2015; Gasiewicz, Singh, & Bennett, 2014; Kimura, Ding, & Tohyama, 2016; Lahvis et al., 2005; Quintana & Sherr, 2013; Singh et al., 2014; Stockinger, Di Meglio, Gialitakis, & Duarte, 2014). Some of these functions may involve natural or endogenous ligands such as metabolites generated by the microbiome, tryptophan metabolites, or lipid‐derived molecules (Bessede et al., 2014; Hubbard, Murray, & Perdew, 2015; McMillan & Bradfield, 2007; Moura‐Alves et al., 2014).…”
Section: Ahr Pathwaymentioning
confidence: 99%
“…This suggests that it has a fundamental role in cellular physiology. In addition, several results from studies with AhR knockout mice have demonstrated functions that need the AhR under developmental stages and for physiologic homeostasis processes without exogenously administered ligands (Gasiewicz et al, 2014).…”
Section: Aryl Hydrocarbon Receptor In the Lungmentioning
confidence: 99%
“…Accumulating evidence in mouse embryonic stem cells and hematopoietic system suggests that AHR is involved in regulation of stem/progenitor cells (Singh et al, 2009;Gasiewicz et al, 2014;Wang et al, 2016;Unnisa et al, 2016). Evidence for stem/progenitor cells as target of human AHR has also been obtained in studies of chloracne, the hallmark of dioxin toxicity (Ju et al, 2011;Bock, 2016).…”
Section: Ahr Functions In Stem/progenitor Cell Homeostasismentioning
confidence: 89%